AGROINDUSTRI PENYULINGAN MINYAK DAUN CENGKEH (Studi Kasus di Desa Cangkring Kecamatan Ngadirojo Kabupaten Pacitan) - Budiawan, Adi (Berkala Ilmiah AGRIDEVINA, 2016)
Clove leaf oil can be produced in Indonesia because the rawmaterial of clove leaves is available abundantly in ourcountry, with the aim of sufficient clove leaf oil for bothdomestic andexport. To produce clove leaf oil products, thecompany still uses simple equipment with manual power, buthas been able to produce clove leaf oil with quality andquantity in accordance with existing quality standards. Thisstudy aims to 1 Know the aspects of production technologyused in clove leaf oil distillation. 2 Knowing the productionprocess of clove leaf oil distillation. 3 Analyze the clove leafoil distillation agroindustry economically. The analysis usedin this study is the Cost of Process Cost Method, BEPAnalysis, Profit or Profit Concept, Efficiency Concept Effort.Production facilities used in the form of raw materials,auxiliary materials, packaging, machinery and equipment, aswell as energy. Clove leaf oil can be extracted by steamdistillation because clove leaf oil is one of the oils that is notdamaged by heat. Steam distillation can be distinguishedinto two: direct distillation and indirect distillation. Receivedrevenue of Rp. 999.000,-with sales amount 300 kg of cloveleaf oil and with price 1 kg of clove leaf oil Rp. 30.000,-sothe profit earned is Rp. 999.000,-with the cost of Rp.8.001.000,-.Keywords: Essential oil, Clove Leaf, Refinery, Agroindustry